Reduction of cyanide concentration in cassava by lactic acid bacteria fermentation: A meta-analysis - Jayanegara M. Asyam; Palupi Eny; Jayanegara Anuraga (BIO Web of Conferences)
Cassava is a major staple food for humans in many countries, particularly in tropical regions. However, it also contains a toxic compound, cyanide. Various treatments are required to alleviate these toxins before they can be safely consumed by humans. This study aimed to investigate the effect of cassava fermentation by lactic acid bacteria (LAB) on cyanide concentration using a meta-analysis method. Nine articles, comprising 20 comparisons, were integrated into a database. The effect size used was based on the ln response ratio (ln RR). The integration of effect sizes from different studies was based on a random effect model with the DerSimonian-Laird algorithm. The results revealed that LAB fermentation reduced the total cyanide concentration with an effect size of ˗0.667 (lower bound -0.836; upper bound ˗0.499; P<0.001) or equal to an average cyanide reduction of 48.7%. The fermentation period had no effect on cyanide reduction. Fermentation of cassava enhanced lactic acid concentration and LAB population with an effect size of 2.305 (about 10 folds increase; P<0.001) and 0.757 (P<0.001), respectively. Fermentation also decreased the pH of cassava (effect size ˗0.407; P<0.001). In conclusion, LAB fermentation is an effective processing technique for reducing the poisonous cyanide in cassava.